2020
DOI: 10.3390/jcm9020535
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Cervical Myelopathy: A Brief Review of Past Perspectives, Present Developments, and Future Directions

Abstract: Degenerative cervical myelopathy (DCM) is the most common cause of spinal cord injury in developed countries; its prevalence is increasing due to the ageing of the population. DCM causes neurological dysfunction and is a significant cause of disability in the elderly. It has important negative impacts on the quality of life of those affected, as well as on their caregivers. DCM is triggered by a variety of degenerative changes in the neck, which affect one or more anatomical structures, including intervertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 61 publications
2
49
0
6
Order By: Relevance
“…Degenerative Cervical Myelopathy (DCM) is a debilitating, progressive, degenerative spine condition, characterized by a neurological dysfunction due to static and dynamic injury of the spinal cord in the cervical spine (1,2). DCM affects quality of life to an extent greater than other chronic debilitating diseases, including hypertension and diabetes, and presents with an incidence of hospitalizations estimated at 4.04/100,000 person-years (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Degenerative Cervical Myelopathy (DCM) is a debilitating, progressive, degenerative spine condition, characterized by a neurological dysfunction due to static and dynamic injury of the spinal cord in the cervical spine (1,2). DCM affects quality of life to an extent greater than other chronic debilitating diseases, including hypertension and diabetes, and presents with an incidence of hospitalizations estimated at 4.04/100,000 person-years (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Furthermore, studies reporting on natural history of DCS (risk of progression, instability, and space available for the cord) are 1 University of Geneva, Switzerland limited. 4 On the other hand, numerous articles discussed specific pathological criteria (for instance, ossification of the posterior longitudinal ligament, age, magnetic resonance imaging [MRI] signal change) 10,11 within the domain of degenerative cervical myelopathy (DCM) and their impact on baseline severity, surgical outcome, and management strategies. Given that DCS is a consequence of the degeneration cascade (including disc degeneration and hypertrophic arthropathy of the facet joints and ligaments), which is also true for other subsets of DCM, and typically manifests in the ageing spine, it is tempting to postulate that presence of DCS can directly influence the severity of DCM and outcome (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Degenerative Cervical Myelopathy (DCM) is becoming a growing public healthcare burden, attributable principally to an aging population. It represents a group of degenerative changes of the cervical spine that result in static and dynamic compression of the spinal cord, leading to subsequent chronic inflammatory and mechanical damage to neural tissue [ 1 , 2 , 3 ]. DCM represents the most common cause of spinal cord impairment in the developed world, leading not only to a decrease in the quality of life of those affected but also is increasingly recognized as a public healthcare and social burden [ 3 , 4 ].…”
mentioning
confidence: 99%
“…DCM represents the most common cause of spinal cord impairment in the developed world, leading not only to a decrease in the quality of life of those affected but also is increasingly recognized as a public healthcare and social burden [ 3 , 4 ]. Over the past few years, research on this topic has allowed for a better understanding of its pathological features, natural history, diagnosis, severity, associated conditions, treatment thresholds, and outcomes, collectively helping to provide a better understanding of the condition [ 1 , 5 ]. However, this research effort has also clearly demonstrated the ongoing knowledge gaps that exist and require further investigation [ 2 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation